Tailoring Local–Global Structures via Hot Deformation for High-Performance BiSbSe3 Thermoelectrics - Xiaowei Shi; Saichao Cao; Yu Yan; Quanwei Jiang; Huijun Kang; Rongchun Chen; Enyu Guo; Zongning Chen; Li-Dong Zhao; Tongmin Wang (Journal of the American Chemical Society, 2026)
Abstract Enhancing carrier concentration (n) is widely regarded as a core strategy for advancing high-performance thermoelectric (TE) materials. However, this approach is often limited by a concomitant decline in carrier mobility (μ). To surmount this trade-off, a synergistic integration combining composite engineering and hot deformation processing was employed to synergistically optimize both n and μ in BiSbSe3. Microstructural analysis reveals that this dual processing route drives a local–global structural evolution, involving texture formation, dynamic recrystallization, precipitation of Cu-rich secondary phases (CuSbSe2), incorporation of interstitial Cu atoms, and enhanced short-range ordering. As a result, the optimized n and tailored carrier transport pathways lead to reproducible and substantially enhanced electrical conductivity and power factor. Meanwhile, interstitial atoms, dislocations, subgrain boundaries, and heterogeneous interfaces collectively create a multiscale phonon scattering network, effectively reducing lattice thermal conductivity. Consequently, the peak ZT value along the out-of-plane direction is dramatically enhanced from ∼0.06 for pristine BiSbSe3 to ∼1.3 at 723 K for the BiSbSe3 + 2 mol % CuI + 1.8 mol % Cu sample subjected to single-pass hot deformation. This peak ZT value surpasses the highest reported value at the same temperature, with the Vickers hardness of the modified sample concurrently improved. This work elucidates the micromechanisms through which hot deformation synergistically regulates TE properties via tailoring of local–global structural modifications, laying a solid foundation for future commercialization.